Comparison of Continuation of Low-Molecular-Weight Heparin versus Switching to Unfractionated Heparin in the Peripartum - Enakpene, Christopher A.; Pontarelli, Kristina N.; Della Torre, Micaela (American Journal of Perinatology, 2020)
Objective This study aimed to determine whether switching from low-molecular-weight heparin (LMWH) to unfractionated heparin (UFH) or its continuation in the peripartum affected anesthesia choice or bleeding complications.Study Design A retrospective cohort study of 189 anticoagulated pregnant women who delivered at the University of Illinois at Chicago Hospital and Health Science System from 2005 to 2016. Demography, anesthesia choice, and bleeding complications were compared between the two groups.Results There were 138 (73%) women on LMWH versus 51 (27%) who switched from LMWH to UFH during the peripartum. The demographics were similar, 123 women were on prophylactic: 81 (66%) were on LMWH and 42 (34%) switched to UFH. Of the 66 women on therapeutic anticoagulation, 57 (86%) continued on LMWH, while 9 (14%) switched to UFH. No difference in neuraxial anesthesia type received: 42 (82.4%) versus 108 (79.7%) women (odds ratio: 1.20, 95% confidence interval [CI]: 0.52–2.73, p = 0.837). Bleeding complications more than 1,000 mL, 6 versus 10% (relative risk [RR]: 0.58, 95% CI: 0.17–1.94, p = 0.380) and relaparotomy due to hemoperitoneum, 2% in either group (RR: 0.9, 95% CI: 0.10–8.48, p = 0.930) were similar in the two groups regardless of time of last injection.Conclusion Anesthesia type and rate of bleeding complications were similar between women on LMWH and UFH during the peripartum.
Keywords: anticoagulation; pregnancy; low-molecular-weight heparin; unfractionated heparin; peripartum; bleeding complication; neuraxial anesthesia